Flexphores : a flexible interaction for web based personal digital photo retrieval system - Ismail, N. A.; O'Brien, A. (Penerbit UTM Press, 2008)
This paper describes the development of multimodal user interface for web based personal digital photo retrieval (FlexPhoReS) prototype. FlexPhoReS is an experimental system that enables digital photo users to accomplish photo retrieval tasks (browsing, keyword and visual example searching (CBIR» using either mouse and keyboard input modalities or mouse and speech input modalities. It extends input modalities of web based photo retrieval technologies by offering alternative input modalities through a muItirnodal user interface in the World Wide Web environment. Our user study with 20 digital photo users showed that the prototype user interface for web based personal digital photo retrieval system-is acceptable to the users.